Floor crossing and nascent democracies - a neglected aspect of electoral systems?: The current South African debate in the light of the Indian experience - Spieß, Clemens; Pehl, Malte (Verfassung und Recht in Übersee, 2004)
eBook: Floor Crossing and Nascent Democracies - a Neglected Aspect of Electoral Systems? The Current South African Debate in the Light of the Indian Experience (ISSN0506-7286) von aus dem Jahr 2004
Gesehen am 28.06.2021
Keywords: Indien; Südafrika